Pre- and Postoperative Brain Magnetic Resonance Imaging Findings and Their Relationship to Neurodevelopment in Newborns with Congenital Heart Disease - Kosiorek, Agnieszka; Justus Liebig University Giessen (My University, 2022)
Introduction: Numerous studies identified potential risk factors for adverse neurodevelopmental outcome in infants with congenital heart disease (CHD). Nevertheless, little is known about neurologic sequelae within CHD subpopulations. The aim of the study was to illustrate perioperative variables and abnormal brain MRI findings in a specific CHD subpopulation of infants who were not exposed to deep hypothermic circulatory arrest (DHCA) during their first heart surgery. A secondary aim was to determine the impact of clinical characteristics, perioperative course and neuroimaging abnormalities on neurological outcome in this subpopulation of CHD patients. Methods: Infants with CHD who underwent open heart surgery without DHCA between 2009 and 2017 were identified from a cardiac surgery database. Full term infants < 10 weeks of age at the time of surgery who received both a pre- and post-operative brain MRI were included. Patients with genetic neurodevelopmental disorders were excluded. Brain Injury Scores (BIS) were assigned to pre- and postoperative brain MRIs. Variables were examined for association with neurological outcome of the patients at ≥ 12 months of age using the Pediatric Stroke Outcome Measure and Glasgow Outcome Scale-Extended. Results: In the study, 42 infants were enrolled and evaluated, of which 69 % (n = 29) participated in a neurological follow-up at ≥ 12 months of age. Prolonged stay in the intensive care unit (ICU, P = 0.003), extended mechanical ventilation (P = 0.031), modified Blalock-Taussig (MBT) shunt procedure (P = 0.005) and presence of seizures in the postoperative period (P = 0.005) were associated with worse neurological outcome. In the multivariable analysis postoperative cerebral infarction and/or intraparenchymal hemorrhage (IPH) were linked to adverse outcome (P = 0.018). Total BIS scores did not predict the outcome. Conclusion: Adverse neurologic outcome in infants with CHD after infant cardiac surgery without DHCA was associated with prolonged ICU stay, extended mechanical ventilation, MBT shunt, presence of postoperative seizures as well as postoperative stroke and/or IPH.
Keywords: ddc:610